Progression in nano-botanical oral hygiene solutions: The Dawn of biomimetic nanomaterials - Aqsa Arif; Muhammad Sharif Khar; Nariman Shahid; Waqar Aman; Joham Javed; Amina Rubab; Mashal Nayab; khadija mastoor; Rabia Arshad; Abbas Rahdar; Sonia Fathi-karkan; Zelal Kharaba; et al. (Elsevier, 2024)
Pathogenic bacteria consistently pose significant challenges within the oral mucosal environment by altering bioflora, biofilm development, and enamel demineralization, thus leading to extensive clinical resources for treatment. This review aims to gather suitable and novel information in terms of providing advanced bio-inspired therapeutic facilities to alleviate the burden of treatment on both the patient and medical infrastructure. Botanical nanoparticle-based mouthwashes have been synthesized using mostly green synthesis technology. Botanical nanoformulations-based mouthwashes are efficient for maintaining microbial flora and mimicking natural extracellular matrix (ECM) components. Furthermore, dental caries can also be treated by these nanoparticles through the promotion of enamel remineralization and bacterial growth suppression. These nature-inspired oral rinses/mouthwashes confer significant advantages relative to their synthetic counterparts, particularly in terms of safety, efficacy, and formulation simplicity. The potential applications of these bioinspired nanomaterials extend beyond wound healing and dental infection management, heralding a promising frontier in oral health restoration. The diversified range of these nanomaterials, from Propolis, Miswak, and Chitosan nanoparticles (NPs) to pomegranate extract and Matricaria chamomilla L. extract-based mouthwashes, introduces an exciting new dimension to oral care.